Mutual complementarity of arable land use in the Sino-Africa trade: Evidence from the global supply chain. (May 2023) - Ji, Xi; Su, Pinyi; Liu, Yifang; Wu, Guowei; Wu, Xudong
Abstract: This study targets participants of the Forum of China-Africa Cooperation (FOCAC) and aims to comprehensively analyze the arable land use transfer between China and Africa. We apply the multiregional input-output analysis to assess embodied arable land use and depict multifaceted changes of arable land use transfer embodied in the Sino-Africa trade from 1990 to 2015. Results reveal that: (1) China is a net importer of embodied arable land use in the Sino-Africa trade to meet its expanding domestic consumptive demand; the arable land use transfer in the Sino-Africa trade is less than that in EU-Africa and US-Africa trade; (2) there is a decline in the arable land use intensities for both China and Africa and a sharp decrease in the gap between the two intensities since the establishment of FOCAC; (3) the textiles and manufacturing sectors are the two largest contributors to the arable land use transfer from China to Africa, whereas agriculture sector is the largest contributor from Africa to China; (4) the share of China's arable land use originating from foreign regions increases from 2 % in 1990 to 23 % in 2015; approximately 40 % of arable land resources exploited locally in Africa are for final consumption abroad; China's arable land use that originates from Africa grows at an average annual rate of 11 %. Our findings affirm the positive effects of the Sino-Africa trade on arable land reallocation, and lend support to optimizing the trade structure in China and Africa in order to maximize usage of arable land resources. Highlights: Arable land use transfer embodied in the Sino-Africa trade is studied. China is a net importer of embodied arable land use in the Sino-Africa trade. The gap between China's and Africa's arable land use intensities narrowed since the establishment of FOCAC. Sectoral contributions and source-to-sink properties of arable land use transfer are identified.